Safety and efficacy of doxycycline in the treatment of rosacea - Sheila Valentín; Adisbeth Morales; Jorge L Sánchez; et al (Dove Medical Press, 2009)
Sheila Valentín, Adisbeth Morales, Jorge L Sánchez, Abimael RiveraDepartment of Dermatology, University of Puerto Rico, School of Medicine, San Juan, Puerto RicoAbstract: Rosacea is a common, chronic, skin condition characterized by recurrent episodes of facial flushing, transient or persistent erythema, papules, pustules, and telangiectasias, in a symmetrical facial distribution. The etiology of rosacea remains unknown and this condition represents a therapeutic challenge because of its chronic nature, progression, potential for disfigurement and psychological impact. Although there is no curative therapy for rosacea, the most widely used systemic agents are oral tetracycline derivatives, including tetracycline, doxycycline, and minocycline. This article reviews the available evidence for the use of doxycycline, a second-generation tetracycline, in the treatment or rosacea.Keywords: rosacea, doxycyline, tetracyclines